Co2+ and Cr3+ ions removal from wastewater by using nanostructural hydroxyapatite. (3rd November 2022) - Phuong, Nguyen Thu; Thom, Nguyen Thi; Nam, Pham Thi; Van Trang, Nguyen; Huong, Tran Thi Thu; Hai, Do Thi; Thu, Le Phuong; Osial, Magdalena; Thanh, Dinh Thi Mai
Abstract: Due to the growing pollution of the environment, water purification methods have to be improved. One of the most effective solutions is the removal of heavy metal ions by porous materials, including hydroxyapatite. Lao Cai Province in Vietnam has a tremendous reservoir of apatite ore that can be a precursor for nanostructural materials. In this paper, we refer to the recent studies on removing heavy metal salts, including the cobalt and chromium ions, from the wastewater by the nanostructural hydroxyapatite obtained from the apatite ore gained in the Lao Cai Province. The measurements were performed according to the pH, mass of the adsorbent addition into the real wastewater solution, and time exposition onto the adsorbent; and the suitable condition is a dose of modified apatite of 1 g/L; contacting time of 60 minutes and 6 g/L and 15 minutes in the pH range from pH0 (3.76 and 6.57) to neutral pH corresponding to Cr 3+ and Co 2+ . We show that just a small amount of the nanostructural hydroxyapatite can work efficiently to remove the chromium and cobalt ions from the solution with maximum adsorption capacity is 70.37 mg/g and 13.52 mg/g, respectively. Abstract :